The Effectiveness Of Primm-flipped Classroom Towards Critical Thinking Skills, Motivation And Achievement In Learning Computer Programming Course Among Undergraduate Students - Almassri, Mirvat A H (2023)
The flipped classroom is a popular approach for improving higher education learning including computer programming. Learning the concept of programming and its foundation is a difficult task for some students, resulting in poor academic achievement and estrangement. Computer programming requires critical thinking skills, which Palestinian undergraduate students lack. As a result, there is a need to use appropriate methods to personalise learning. The flipped classroom is important in computer programming learning because it makes the subject more interesting and appealing. There were gaps in research studies conducted in Palestinian universities concerning the effectiveness of flipped learning in computer programming learning. This study investigates and describes the effects of flipped classroom in learning computer programming towards critical thinking skills, motivation and achievement among undergraduate Palestinian students. The topic is important because it has the potential to improve the programming learning process in universities. A mixed-mode design employs both a quantitative (Quasi-experimental) and a qualitative approach (Interviews). The study sample included 123 undergraduate students from Palestine Technical University Kadoorie in Palestine. The students were divided into two groups: flipped classroom (experimental group) and non-flipped classroom (control group).